Rapid disease progression after discontinuation of lenvatinib in thyroid cancer. Issue 11 (March 2020) - Yamazaki, Haruhiko; Sugino, Kiminori; Matsuzu, Kenichi; Masaki, Chie; Akaishi, Junko; Hames, Kiyomi; Tomoda, Chisato; Suzuki, Akifumi; Uruno, Takashi; Ohkuwa, Keiko; Kitagawa, Wataru; Nagahama, Mitsuji; et al.
Abstract : Abstract: Some thyroid cancer patients experience a rapid disease progression after the discontinuation of tyrosine kinase inhibitors (TKIs), which is called flare phenomenon. The incidence of the flare phenomenon of epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) ranged from 4% to 11.1% and the median time to occurrence of the flare phenomenon ranged from 7 to 12 days in previous reports. In this study, we investigate the timing and incidence of the flare phenomenon in thyroid cancer patients treated with lenvatinib. The records of patients treated with lenvatinib were retrospectively reviewed. The primary outcomes were the incidence rate and timing of the flare phenomenon after the discontinuation of lenvatinib. The flare phenomenon was defined as death, hospitalization attributable to tumor progression, or unexpected event (e.g., pleural drainage) within 1 month of lenvatinib cessation. We excluded patients with progression of underlying diseases other than thyroid cancer or infection, those in whom the disease progressed, or those who died without achieving a clinical response (stable disease, partial response, or complete response). In total, 8 (14.3%) of the 56 patients experienced the flare phenomenon. The median time from lenvatinib cessation to the flare phenomenon was 9 (range, 4–30) days. Three patients in the flare group died within 1 month of lenvatinib cessation without an imaging evaluation. The remaining 5 patients had dyspnea and pleural effusion, and pleural drainage was performed in 3 of the 5 patients. Lenvatinib was resumed in 4 of the 8 patients in the flare group. Median overall survival (OS) was 15.1 months in the flare group and 41.9 months in the non-flare group. The OS tended to be poor in the flare group than in the non-flare group; however, this difference was not statistically significant ( P  = .051). In lenvatinib treatment for thyroid cancer, the incidence and timing of the flare phenomenon were similar to those observed with other TKIs. OS tended to be poor in the flare group than in the non-flare group. Further studies are needed to determine the mechanism of the flare phenomenon and establish measures and treatment policies.